Variables Affecting the Repayment of the Community Business Credit KUR by Farmers in Coffee Farming - Refni Alawiyah; Munajat Munajat; Rini Efrianti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Coffee productivity experiences fluctuations where production from year to year always fluctuates but judging from the development of the business world which is increasing, especially in agriculture with coffee producing centers. Natural coffee cultivation activities certainly require maintenance costs which are not a few things this also cannot meet from one's capital alone and requires additional capital from other parties. In doing this business, not all farmers have sufficient capital to run their business, so the community needs additional capital to increase their business. One of the financial institutions that provide loans is bandages through the KUR guarantee program, which is 80 percent of which is indeed allocated to the agricultural sector. Meanwhile, in South OKU District itself, almost all coffee farmers are banking customers who get KUR credit facilities from several banks in Muara Dua OKU Selatan. During the pandemic, it can be said that it has not experienced the problem of bad debts which is so meaningful. So this attracted researchers to further examine the factors that affect the return of KUR by farmers in coffee farming in Runjung Agung District, Ogan Komering Ulu Selatan District. The focus of this study will be to review more deeply what factors affect the repayment of KUR on coffee farming in Runjung Agung District, Ogan Komering Ulu Selatan District (ownership status, income from coffee farming, land area, coffee farming costs, number of family dependents, loan amount, and credit repayment period)